قصيدة الوعي السياسي الجاهلية دراسة وفق نظرية اللأفعال الكلامية (Journal of Hama University, 2025)
The research studies the pre-Islamic political awareness poem which divulges the depth of the tribal affiliation of the pre-Islamic poet. It also invests speech act concept in explaining the content of pre-Islamic political awareness poem. Then, it provides a view of the status of the pre-Islamic poet, proves the political awareness concept and explains speech acts in Western linguistic and Arabic rhetoric studies. It elaborates on the performance of constatives and performatives in the content of pre-Islamic awareness poem. To achieve its purpose, the research used the stylistic approach to study the content of the pre-Islamic political poem based on the Speech Acts Theory. The research adopted the historical theory to comprehend the general context in which the poet poetically conveyed his political message to his tribe. It proved that political guidance is a poetic, and its main motive is the poet’s interest in the existence of the tribe, preserving its existent, managing its affairs and directing it to avoid dangers. The research demonstrates the awareness-raising role of the poet in the tribe, and accentuates the poet’s consciousness which prompted /encouraged/urged the poet to tackle the meaning of political guidance in his poetry. The research states that most of the topics of pre-Islamic political awareness poem (i.e political reporting, describing the condition of female captives after invasion, comparing the status of the tribe to that of the enemy) neither describe a reality nor can be described as true or false, rather they initiate an act. The power of the constative act appears in the change and guarding against the situation more than in informing about the invasion and reporting its consequences. Performatives are clear in elucidating means of survival, maintaining tribe existence and seeking reform.
Keywords: Political awareness, pre-Islamic poem, speech act, speech performance , performative act, influential act.